2021
DOI: 10.1111/bph.15623
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget molecule, PTUPB, to treat diabetic nephropathy in rats

Abstract: Background and Purpose: Diabetic nephropathy is a common complications related to high morbidity and mortality in type 2 diabetes. We investigated the action of the dual modulator, PTUPB, a soluble epoxide hydrolase and cyclooxygenase-2 inhibitor against diabetic nephropathy.Experimental Approach: Sixteen-week-old type 2 diabetic and proteinuric obese ZSF1 rats were treated with vehicle, PTUPB or enalapril for 8 weeks. Measurements were made of epoxyeicosatrienoic acids, thromboxane B 2 (TBX 2 ) and prostaglan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…Indeed, combined sEH and COX-2 inhibition with PTUPB decreased sorafenib-induced nephrotoxicity. Our present finding is consistent with the previous studies using Zucker diabetic rats, where PTUPB was also found to decrease kidney injury and proteinuria ( Hye Khan et al, 2016 ; Khan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, combined sEH and COX-2 inhibition with PTUPB decreased sorafenib-induced nephrotoxicity. Our present finding is consistent with the previous studies using Zucker diabetic rats, where PTUPB was also found to decrease kidney injury and proteinuria ( Hye Khan et al, 2016 ; Khan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…33 PTUPB also decreased inflammation and fibrosis in the kidney and liver of obese ZSF-1 hypertensive and diabetic rats. 33 PTUPB treatment exhibited anti-inflammatory and anti-fibrotic actions in animal models of sepsis, non-alcoholic liver disease (NAFLD), and pulmonary fibrosis. 36,37,38,39 Taken together, these studies demonstrate the potential for PTUPB to decrease inflammation and oxidative stress and combat fibrosis to slow the progression of diabetic kidney injury.…”
Section: Ptupbmentioning
confidence: 80%
“…19,31,32 The ability for PTUPB to increase EETs and lower COX-2 metabolites without significantly altering other arachidonic acid metabolites has been demonstrated in multiple studies. 33,34,35 These studies have not extensively evaluated the effects of PTUPB on mRNA or protein expression of lipoxygenase, CYP4A, or CYP2C enzymes. The effects of PTUPB on glucose homeostasis and kidney injury were first evaluated in ZDF rats treated in a preventive manner for two months.…”
Section: Ptupbmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological manipulation of sEH by t-AUCB in db/db mice significantly attenuated diabetic renal injury through reliving mitochondrial dysfunction and ER stress via inhibition of inflammation and autophagy [109]. A COX-2/sEH dual inhibitor PTUPB also significantly reduced urinary MCP-1 levels and renal cytokine expression, and therefore alleviated the development of diabetic nephropathy in rat [110]. In context of diabetic retinopathy, expression of CYP2B2 was significantly downregulated and 11,12-EET promoted angiogenesis in the retina under ischemia and hypoxia caused by diabetes [111,112] (Figure 4).…”
Section: Eets and Diabetic Complicationmentioning
confidence: 97%